Kesiapan Aparatur Desa Dalam Pelaksanaan Pengelolaan Keuangan Desa Secara Akuntabilitas Sesuai Undang-Undang Nomor 6 Tahun 2014 Tentang Desa ( Studi pada Beberapa Desa di Kabupaten Pidie) - Husna, Saifatul; Abdullah, Syukriy (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The laws of Republic Indonesia No. 6 year 2014 concerning the Villages is a product of the reformation era that became initial form of village autonomy in governing nor managing the Villages finance. Considering the funds received by the village is sufficiently a large number and keeps increasing every year, then in governing and managing villages finance, it required for reliable village apparatuses capacity and other appropriate fasilities in order to make the implementation more purposeful and more accountable. This study was conducted to provide empirically overview about the readiness of village apparatuses in implementating village finance in accountability in accordance to Law No. 6 of 2014 concerning the village. This research was conducted in eight villages in District of Pidie, consists of, Bintang Hu, Dayah Baroe, Nien Lambideng, Arusan, Deyah Blang, Ribeun, and Lampoh Sirong. This research is descriptive study which used qualitative data by conducted interview and documentation. The result shows that in eight villages sampled, only one village were not ready in the planning process and accountability of village finance. The problem faced by village apparatuses in managing villages finance is the lack of qualified human resources and have understanding about management of villages finance, it results the village apparatuses prefer to use third parties services in preparing and formulating the reports required.Keywords: The Laws of Village, Village Apparatuses Capacity, Villages Finance Management, Accountability